Designing a Kadazandusun language learning application with gamification - Asni Tahir; Jane Vylorra Badimin; Siti Hasnah Tanalol; Mohd Shamrie Sainin; Norazlina Khamis (Pusat e-pembelajaran, UMS, 2023)
The KadazanDusun Language, the native tongue of the KadazanDusun ethnic community in Sabah, serves as the focal point of this academic endeavor. Specifically, this research centres on the creation of an Android-based Mobile Learning Application for KadazanDusun Language, integrating gamification as a pedagogical approach. The objective is to create an engaging and interactive platform that facilitates children in acquiring KadazanDusun vocabulary through gamified learning experiences. Gamification, defined as the strategic infusion of game design elements into non-gaming contexts, is instrumental in enhancing participant engagement and involvement. The potential advantages of this application are multifaceted, extending to its capacity to provide a platform for educational activities and help learners to hone their language skills through interactive activities embedded within the application. To develop this application, an iterative ADDIE (Analysis, Design, Development, Implementation, and Evaluation) methodology was adopted. This approach aligns with agile project management principles, making it well-suited to the project by streamlining planning stages and concentrating efforts on prototyping, thereby optimizing time and resources. The application's content derives from a comprehensive KadazanDusun textbook, encompassing various thematic modules such as numerals (numbul), colors (Warana), anatomical terminology (Boogian Tinan), and familial relationships (paganakan). Preliminary findings from the prototype design phase indicate positive user feedback, highlighting the promising potential of this educational tool.